Computational fluid dynamic simulations and heat transfer characteristic comparisons of various arc-baffled channels - Menni, Younes; Ameur, Houari; Yao, Shao-Wen; Amraoui, Mohammed Amine; İnç, Mustafa; Lorenzini, Giulio; Ahmad, Hijaz (De Gruyter Poland Sp Z O O, 2021)
In this analysis, the baffling method is used to increase the efficiency of channel heat exchangers (CHEs). The present CFD (computational fluid dynamics)-based work aims to analyze the constant property, steady, turbulent, Newtonian, and incompressible fluid flow (air), in the presence of transverse-section, arc-shaped vortex generators (VGs) with two various geometrical models, i.e., arc towards the inlet section (called arc-upstream) and arc towards the outlet section (called arc-downstream), attached to the hot lower wall, in an in-line situation, through a horizontal duct. For the investigated range of Reynolds number (from 12,000 to 32,000), the order of the thermal exchange and pressure loss went from 1.599-3.309 to 3.667-21.103 times, respectively, over the values obtained with the unbaffled exchanger. The arc-downstream configuration proved its superiority in terms of thermal exchange rate by about 14% than the other shape of baffle. Due to ability to produce strong flows, the arc-downstream baffle has given the highest outlet bulk temperature.
Keywords: Thermal exchange rate; pressure loss; baffling method; turbulent forced-convection; numerical solution